Synergistic activation of diclofenac, by three Phytochemicals; a study in candida albicans model - SUPRIYA PANDURANG MORTALE; SHIVKRUPA DEVRAO HALBANDGE; BHAGYASHREE SHRIDHARRAO BANSODE; SANKUNNY MOHAN KARUPPAYIL (International Journal of Pharma and Bio Sciences, 2017)
Device related infection cause by Biofilm forms of Canida albicans. are life threatening because of their increased tolerance of antifungal drugs hence novel treatments are needed. Combinatorial therapy involving phytochemicals and antifungal drugs would be an effective approach against drug resistant Candida biofilms. Eugenol, Thymol and Carvacrol are the three phytochemicals were tested in combination with Diclofenac sodium against planktonic and biofilm forms of C.albicans ATCC 90028 and one clinical isolate of C. albicans isolated from sputum of a male patient suffering from Candida infection in Government Medical college (GMC 3 is identification code).Diclofenac sodium is a non steroidal anti-inflammatory drug which is blocked the synthesis of mammalian prostaglandin by inhibiting cyclooxygenase isoenzymes.Activities of various combinations were analyzed by chequerboard format. The interaction between three phytochemicals with Diclofenac sodium were determined by calculating fractional inhibitory concentration indices (FICI) and results obtained by XTT metabolic assay were confirmed by scanning electron microscopy. Three phytochemicals in combination with Diclofenac sodium showed synergistic interaction against planktonic assay. Eugenol and Thymol combination with Diclofenac sodium showed synergistic interaction against developing biofilm of C.albicans.Whereas Thymol and Carvacrol combination with Diclofenac sodium showed synergistic interaction against mature biofilms of C.albicans. This study for the first time indicates that Diclofenac sodium increases efficacy of three phytochemicals against biofilms of C.albicans.